Effects of exercise training on atrophy gene expression in skeletal muscle of mice with chronic allergic lung inflammation - Durigan,J.L.Q. (2009)
We evaluated the effects of chronic allergic airway inflammation and of treadmill training (12 weeks) of low and moderate intensity on muscle fiber cross-sectional area and mRNA levels of atrogin-1 and MuRF1 in the mouse tibialis anterior muscle. Six 4-month-old male BALB/c mice (28.5 ± 0.8 g) per group were examined: 1) control, non-sensitized and non-trained (C); 2) ovalbumin sensitized (OA, 20 µg per mouse); 3) non-sensitized and trained at 50% maximum speed _ low intensity (PT50%); 4) non-sensitized and trained at 75% maximum speed _ moderate intensity (PT75%); 5) OA-sensitized and trained at 50% (OA+PT50%), 6) OA-sensitized and trained at 75% (OA+PT75%). There was no difference in muscle fiber cross-sectional area among groups and no difference in atrogin-1 and MuRF1 expression between C and OA groups. All exercised groups showed significantly decreased expression of atrogin-1 compared to C (1.01 ± 0.2-fold): PT50% = 0.71 ± 0.12-fold; OA+PT50% = 0.74 ± 0.03-fold; PT75% = 0.71 ± 0.09-fold; OA+PT75% = 0.74 ± 0.09-fold. Similarly significant results were obtained regarding MuRF1 gene expression compared to C (1.01 ± 0.23-fold): PT50% = 0.53 ± 0.20-fold; OA+PT50% = 0.55 ± 0.11-fold; PT75% = 0.35 ± 0.15-fold; OA+PT75% = 0.37 ± 0.08-fold. A short period of OA did not induce skeletal muscle atrophy in the mouse tibialis anterior muscle and aerobic training at low and moderate intensity negatively regulates the atrophy pathway in skeletal muscle of healthy mice or mice with allergic lung inflammation.